Literasi guru terhadap standar mutu guru SMA/MA di kota Bandung - Abdurahman, Ade Mohamad; Ramdhani, Muhammad Ali; Rochman, Chaerul; Basri, Hasan (Tawazun: Jurnal Pendidikan Islam, 2022)
Teacher literacy on teacher quality standards is very important to realize the implementation of quality education. For this reason, through this research, an analysis of the literacy standards of teacher quality has been carried out in order to achieve the success of an education. This study aims to interpret or describe the data accompanied by the achievement of an understanding of teacher quality standards for PAI teachers and non PAI teachers. This research method is descriptive quantitative. Instruments to collect data using questionnaires and interviews. Based on the results of the analysis of literacy data for PAI Teachers and Non PAI Teachers, there are indicators whose presentation qualification scores are lacking, namely the 7th indicator and 6th presentation indicator. The comparison of the percentage of PAI and Non PAI teachers' understanding of teacher quality standards is 82.2% and 78.1%. The results of the triangulation of respondents have two indicators, namely: the 7th indicator from PAI teachers and the 6th indicator from Non PAI teachers, so there needs to be more attention and improvement by schools on the difficulties faced in teacher quality standards. Abstrak Literasi guru terhadap standar mutu guru sangat penting untuk merealisasikan penyelenggaraan pendidikan yang berkualitas. Untuk itu melalui penelitian ini telah dilakukan analisis terhadap literasi standar mutu guru guna mencapai keberhasilan dari suatu pendidikan. Penelitian ini bertujuan untuk melakukan penafsiran atau menggambarkan data disertai dengan ketercapaian pemahaman standar mutu guru pada Guru PAI dan Guru Non PAI. Metode penelitian ini adalah kuantitatif deskriptif. Instrumen untuk mengumpulkan data menggunakan angket dan wawancara. Berdasarkan hasil analisis data literasi Guru PAI dan Guru Non PAI bahwa terdapat indikator yang nilai kualifikasi presentasinya kurang yaitu pada indikator ke-7 dan indikator presentasinya ke-6. Perbandingan persentase pemahaman Guru PAI dan Non PAI terhadap standar mutu guru ialah 82,2 % dan 78, 1 %. Hasil triangulasi responden ada dua indikator yaitu: indikator ke-7 dari Guru PAI dan indikator ke-6 dari Guru Non PAI, sehingga perlu adanya perhatian lebih dan perbaikan oleh sekolah terhadap kesulitan yang dihadapi pada standar mutu guru.